Laparoscopic and luminal endoscopic cooperative surgery can be a standard treatment for submucosal tumors of the stomach: a retrospective multicenter study - Matsuda, Tatsuo; Nunobe, Souya; Kosuga, Toshiyuki; Kawahira, Hiroshi; Inaki, Noriyuki; Kitashiro, Shuji; Abe, Nobutsugu; Miyashiro, Isao; Nagao, Sayaka; Nishizaki, Masahiko; Hiki, Naoki; Society for the Study of Laparoscopy and Endoscopy Cooperative Surgery (Endoscopy, 2017)
Background and study aims We have developed a combined laparoscopic and luminal endoscopic surgery technique for resection of gastric submucosal tumors (SMTs) that can be performed without excessive resection of the stomach. In a multicenter retrospective study we aimed to evaluate the feasibility and safety of laparoscopic and endoscopic cooperative surgery (LECS) for gastric SMT resection.Patients and methods Between October 2007 and December 2011, 126 patients with gastric SMTs underwent LECS at 8 institutions. Patient demographics, tumor histopathologic characteristics, and operative and follow-up data were reviewed.Results 16 tumors (12.7 %) were located in the upper third of the stomach, 88 (69.8 %) in the middle third, 5 (4.0 %) in the lower third, and 17 (13.5 %) at the esophagogastric junction. The mean (standard deviation [SD]) operation time for LECS was 190.2 (66.8) min, with a mean estimated blood loss of 15.1 (38.6) mL. In 2 cases (1.6 %), the procedure was converted to open surgery because of intra-abdominal adhesions or stenosis. Morbidity was found in 6 cases (4.8 %), including 2 leakage, 2 gastric stasis, 1 fever, and 1 cystitis. Histologically, a gastrointestinal stromal tumor (GIST) was found in 86 (68.3 %) cases. The median follow-up period was 54.7 months; no local or distant tumor recurrence was observed and all patients were alive.Conclusions LECS proved to be a safe and feasible procedure for the resection of gastric SMTs, with a reasonable operation time, low bleeding, and an acceptable complication rate in this multicenter study in Japan.